Analisis Deskriptif Manga Matrix Dalam Melihat Unsur Maskulinitas Pada Karakter Pria Game Genshin Impact - Ismaniari, Afina; Adim, Adrio Kusmareza (eProceedings of Management, 2023)
Genshin Impact is a very popular online RPG game, on the Genshin Impact playstore, fifty million people have downloaded it. This game is an open-world RPG type game that has 56 playable characters and 19 of them are male characters. In this game apart from the female characters, the male characters also become sales commodities through the visual design and character stories that have been formed which show the masculine side of each male character. Masculinity cannot escape men in various media and this is a phenomenon that often occurs around us. The phenomenon of male character masculinity and how they are shown in the media for the purpose of increasing their appeal in the media, especially in video games where it is interesting to study. This research was conducted using qualitative research methods with a descriptive approach and a constructive paradigm. In collecting data, researchers used the method of observation and interviews with seven informants. The research results obtained in this study are male characters can be categorized as masculine through body parts and the appearance of the costumes used by male characters always wear neat clothes, tight costumes so that the body shape is visible, costumes that are open so that they show certain parts that can show that he is masculine like muscle and ideal physique. Certain parts that are highlighted through character costumes can give a masculine fantasy to Genshin Impact game players.Keywords- descriptive analysis, Masculinity, Online Game, Genshin impact.